A human-machine interface design to control an intelligent rehabilitation robot system - (:unkn) unknown (IGI Global, 2010)
The demand for rehabilitation increases daily as a result of diseases, occupational and traffic accidents and population growth. In the present time, some important problems occur regarding the rehabilitation period: the transportation of patients, the acquisition and storage of treatment data and the need to support the physiotherapists with intelligent devices. In order to overcome these challenges, the authors hereby propose a human machine interface to control an intelligent rehabilitation robot system designed for the lower limbs. The human machine interface has a structure that is created with a rule-based intelligent controlling structure, combined with conventional controller and an easy-to-use graphical user interface. By means of this interface, the rehabilitation sessions can be stored and members of the rehabilitation team can reach to this stored data via internet. Additionally, the patient can receive treatment in his house. One physiotherapist is able to treat several patients at a time by utilizing this system. The system's capacity has been elaborated through the test results. © 2010, IGI Global.